Leadership matters: preparation program quality and learning outcomes. Issue 2 (19th March 2019) - Ni, Yongmei; Rorrer, Andrea K.; Pounder, Diana; Young, Michelle; Korach, Susan
Abstract : Purpose: Informed by learning transfer theory, the purpose of this paper is to validate the instrument measuring educational leadership preparation program (LPP) quality attributes and graduates' leadership learning and to assess the direct and indirect relationships among them, as reported by program graduates. Design/methodology/approach: This study uses data collected from the 2016 INSPIRE-G Survey, which gathers information from LPP graduates in the USA on their perceptions of program quality and leadership learning. Structural equation modeling was used to determine which program quality factors directly and indirectly influence graduate leadership learning. Findings: The results suggest significant relationships between the assessed LPP attributes and leadership learning. Faculty quality and program rigor and relevance (PRR) had the strongest association with leadership learning, although the relationship between faculty quality and learning was fully mediated by PRR. Internship experiences and peer relationships were also important predictors of leadership learning. Studying with a cohort had a small but positive relationship with graduates' leadership learning, although the relationship was fully mediated by perceived peer relationships. Originality/value: This study further validates the INSPIRE-G Survey and affirms the imperative role of leadership preparation as a predictor to graduate reported learning outcomes and learning transfer. Moreover, this study illustrates the importance of leadership preparation by demonstrating positive relationships between program quality features and reported leadership learning outcomes. Finally, the INSPIRE-G instrument demonstrates its utility as a reliable measure of program quality, which opens the door to large-scale and longitudinal studies of the transfer of learning from leader preparation to practice.